1996
DOI: 10.1111/j.1749-6632.1996.tb33301.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypertension and Propranolol upon Aneurysm Expansion in the Anidjar/Dobrin Aneurysm Modela

Abstract: Propranolol has been suggested to slow aortic aneurysm (AAA) expansion by a mechanism independent of simple blood pressure (BP) reduction. To investigate this hypothesis, we designed a series of experiments to examine the effects of hypertension and propranolol upon AAA expansion. Using an established animal model, we induced AAA in normotensive and genetically hypertensive rats by perfusion of the isolated infrarenal aorta with elastase for two hours. Systolic tail BP was monitored with a plethysmograph. AAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…17 Other investigators have reported that aortic dilatation can be attenuated by a variety of compounds. [15][16][17][18][19][21][22][23][24] In these reports elastin fibers were also preserved as in the animals studied by Dobrin et al…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…17 Other investigators have reported that aortic dilatation can be attenuated by a variety of compounds. [15][16][17][18][19][21][22][23][24] In these reports elastin fibers were also preserved as in the animals studied by Dobrin et al…”
Section: Discussionmentioning
confidence: 78%
“…Since this experimental model exhibits several similarities to human abdominal aortic aneurysms, 14 a variety of laboratories have used it to investigate the pathogenesis and prevention of aneurysm growth. 10,12,13,[15][16][17][18][19][21][22][23][24] In this study, we used a modification of the model that we recently described. 25 An inflammatory response is a critical step in this model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigators have reported that aortic dilatation is attenuated by various compounds in this aneurysm model, [3][4][5][8][9][10][11]13 and that elastin fibers are well preserved under these conditions. [3][4][5][9][10][11]13 These investigators have interpreted these findings as follows: there is very little damage to the elastin fibers immediately after elastase infusion; endogenous proteinases produced either by infiltrating cells or resident mesenchymal cells cause degeneration of the elastin fibers; and the exogenously infused elastase is essential for the induction of endogeneous proteinases rather than the degeneration of elastin fibers directly.…”
Section: Discussionmentioning
confidence: 95%